1974
DOI: 10.1111/j.1423-0410.1974.tb02716.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Heating on Human Albumin1

Abstract: Abstract. Solutions of stabilized 5 and 25% Normal Serum Albumin (Human) fractionated from plasma, placentas, and blends of these sources were subjected to repeated heatings for 120 h at 56 °C, interspersed with storage for 48 h at 4°C. Disc electrophoretic analyses showed that heating some solutions produced a reversible dimerization of the albumin related to the source, protein concentration, and number of heatings. Cellulose acetate electrophoresis showed that repeated heating produced a reduction in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The appearance of the new precipitin arc following the ninth heating is in agreement with our earlier report [3] of a peak in the a-globulin region on cellulose acetate electrophoresis which increased in 5% plasma albumin samples throughout the nine heatings. There was only a slight increase in this peak upon repeated heating of 5% placental or plasmaplacental blends of albumin, and by immunoelectrophoresis there were no additional precipitin arcs in the a-globulin region.…”
Section: Maurer and Subrahmanyamsupporting
confidence: 80%
See 2 more Smart Citations
“…The appearance of the new precipitin arc following the ninth heating is in agreement with our earlier report [3] of a peak in the a-globulin region on cellulose acetate electrophoresis which increased in 5% plasma albumin samples throughout the nine heatings. There was only a slight increase in this peak upon repeated heating of 5% placental or plasmaplacental blends of albumin, and by immunoelectrophoresis there were no additional precipitin arcs in the a-globulin region.…”
Section: Maurer and Subrahmanyamsupporting
confidence: 80%
“…Of the three at each protein concentration, there was one lot each fractionated from plasma, placentas, and a blend of these sources. Antisera were produced to these albumins, which had been com mercially heated for only 10 h at 60 °C, and to the same samples after they had been subjected in our laboratory to as many as nine additional heatings at 56 ± 1 °C for 120 h. Following each heating, the samples were refrigerated for 2 days at 4 °C [3]. New Zealand, female rabbits approx imately 2-3 kg were immunized subcutaneously with 25 mg of albumin in complete Freund's adjuvant (Difco).…”
Section: Maurer and Subrahmanyammentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have reported that increases in the concentration of a compo nent with the electrophoretic properties of a-globulin occurred when NSA [13], plasma [19], or serum [20] was heated. Mackay and Martin [21] found that a component with lower net charge than albumin was formed when purified human albumin was held at 58 °C for 6 h in 0.15MNaCl, pH 6.8 with little or no stabilizer.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of 5% protein solutions was deter mined by cellulose acetate membrane electrophoresis (CAE) as described previously [13], Samples were electrophoresed for 16 min at 250 V in barbital buffer, pH8.6, ionic strength 0.075. Membranes were stained with PonceauS and quantitated by densitometry.…”
Section: Cellulose Acetate Membrane Electrophoresismentioning
confidence: 99%